Prevalence of antibiotic resistance Escherichia coli isolated from Bagmati River water of Kathmandu, Nepal - Puspa Raj Dahal,; Rajendra D. Joshi, (The Bioscan, 2024)
This study assessed the prevalence of antibiotic-resistant Escherichia coli in the Bagmati River, Kathmandu, Nepal. Water samples collected from multiple sites were analyzed for E. coli contamination and subjected to antibiotic susceptibility testing using the Kirby-Bauer disk diffusion method. The results revealed a high level of resistance to commonly used antibiotics such as Ampicillin and Erythromycin, with no zones of inhibition observed for most isolates. Conversely, newer antibiotics like Ciprofloxacin and Gentamicin demonstrated significant effectiveness, with inhibition zones ranging from 21–38 mm and 18–23 mm, respectively. Moderate susceptibility was observed for antibiotics such as Ceftriaxone, Chloramphenicol, and Nitrofurantoin, while resistance patterns for Tetracycline and Cotrimoxazole varied across samples. These findings underscore the alarming levels of antibiotic resistance in E. coli from the Bagmati River, highlighting significant public health risks and the urgent need for enhanced water quality management and antibiotic resistance monitoring in environmental reservoirs.